(untitled) (Namibian Journal for Research, Science and Technology, 2024)
The purpose of the study was to assess of the challenges of gender disparity in the City of Windhoek’s management leadership structures. The results of the study will help the City of Windhoek management in developing leadership and management positions and in addressing gender parity. The study will suggest possible ways on how to eliminate gender barriers and create opportunities in higher leadership and management positions. This study adopted a qualitative approach and case study research design. The researcher purposively selected 15 participants from all departments. Primary data for this study were collected using interview guides. Thematic analysis was used to analyses interview responses. The first key conclusion was that, gender disparity is prevalent at the City of Windhoek. The study revealed eight factors that lead to gender disparity in the city of Windhoek which included lack of implementation of strategic policy, stereotyping leads to discrimination of women in recruitment and selection policies, lack of gender-sensitive budgeting practices, inconsistent gender mainstreaming practices, inadequate gender analysis of information, poor implementation of gender responsive key result areas in performance management plans